Managing Teamwork: A Key Leadership Practice - Kerns, Charles D. (Journal of Leadership, Accountability and Ethics, 2019)
How leaders manage teamwork impacts team performance and well-being. After a brief review of some relevant literature, a practice oriented framework for managing teamwork is offered and the value of engaging in this process is noted. A proven practical coaching approach and real world application example with an executive are provided to help further operationalize the framework. This approach is offered to help enhance a managerial leader’s effectiveness when managing team dynamics and teamwork in workplace settings. Some challenges such as optimizing team behavioral diversity, managing geographically distributed teams, and applying recent developments in neuroscience are considered.